AMBIGUITAS DALAM ANTOLOGI PUISI STADIUM TANAH IBU KARYA ALI SYAMSUDIN ARSI (AMBIGUITY IN THE POETRY ANTHOLOGY STADIUM TANAH IBU BY ALI SYAMSUDIN ARSI) - Abdan, Abdan (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA (JBSP), 2024)
AbstractAmbiguity in the poetry anthology Stadium Tanah Ibu by Ali Syamsudin Arsi. The research method used is descriptive qualitative, namely by analyzing qualitative data of poetry to describe the phenomenon of ambiguity. The purpose of the study is to (1) identify the ambiguity of meaning and interpretation (2) identify the outline of the content of poetry. This study employs a qualitative descriptive approach, aiming to understand phenomena or events in depth through detailed description. The data source is in the form of lines contained in six poetry from the book of poetry Anthology Stadium Tanah Ibu by Ali Syamsudin Arsi. The data analysis technique used is describing the lexical, grammatical, and interpretative meanings that emerge from the lines of the poetry, as well as drawing an outline of the content of poetry. The result of the study in the six poetry shows that there is ambiguity of lexical meaning, grammatical ambiguity, interpretation ambiguity, and outline ambiguity of the content of poetry.Keywords: Lexical ambiguity, grammatical, interpretation, outline of the content of poetryAbstrakAmbiguitas dalam antologi puisi Stadium Tanah Ibu karya Ali Syamsudin Arsi. Metode penelitian yang digunakan adalah deskriptif kualitatif, yaitu dengan mengurai data kualitatif puisi untuk menggambarkan fenomena ambiguitas yang terkandung di dalamnya. Tujuan penelitian untuk (1) mengidentifikasi ambiguitas makna dan penafsiran (2) mengidentifikasi garis besar isi puisi. Penelitian ini menggunakan pendekatan deskriptif kualitatif, yang bertujuan untuk memahami fenomena atau peristiwa secara mendalam melalui penggambaran yang terperinci. Sumber data berupa larik-larik yang terdapat dalam 6 buah puisi dari buku Antologi Puisi Stadium Tanah Ibu karya Ali Syamsudin Arsi. Teknik analisis data dilakukan dengan mendeskripsikan makna-makna leksikal, gramatikal, dan penafsiran yang muncul dari larik-larik puisi, serta menarik garis besar isi puisi. Hasil penelitian pada keenam puisi membuktikan terdapat ambiguitas makna leksikal, ambiguitas gramatikal, ambiguitas penafsiran yang muncul, dan ambiguitas garis besar isi puisi.Kata-kata kunci: Ambiguitas leksikal, gramatikal, penafsiran, garis besar isi puisi